Stress management to reduce prisoner stress levels (Community service training in class I Tanjung Gusta prison, Medan) - Siregar, Rodiatul Hasanah; Hasnida; Raras Sutatminingsih; Saragih, Juliana Irmayanti; Lubis, Arliza Juariani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Penitentiary (prison) is a place where prisoners' room is limited and they are isolated from the community. Prison conditions in Indonesia that are overcapacity now are also conditions that are not ideal for the lives of prisoners. The room must be filled with many people, simple and less varied food, and strict prison rules are stressors that cause prisoners to experience stress. Sarafino (2011) defines stress as a condition where transactions between individuals and the environment lead to a perceived gap between the physical or psychological demands of a situation with the resources of one's biological, psychological, and social systems. The condition of prisoners who experience stress causes them to get angry easily and even behave aggressively which makes the prison atmosphere more uncomfortable. Therefore prisoners need to be helped to manage their stress through Stress Management Training. Stress Management Training given to male prisoners in class I Tanjung Gusta Medan shows the results that stress management techniques taught and applied by prisoners in daily life can reduce the level of stress they experience. Furthermore, by applying stress management techniques routinely, they are expected to be able to manage their stress better so they can live comfortably while serving their sentences in prison.